The Effect of Adding Vaname Shrimp Shell Extract (Litopenaeus vannamei) to Wheat-Based Tekwan on Sensory Preference - Pratama, Melati; Christie, Jessica Maria; Yansah, Marfira (Jurnal Sains dan Teknologi Perikanan, 2025)
Wheat flour tekwan is tekwan made from wheat flour and tapioca.Its flavor is obtained by adding MSG and flavor enhancers. An alternative to adding flavor to wheat flour tekwan is to add shrimp shells, because shrimp shells contain chitin chitosan and glutamic acid from their constituent proteins. The purpose of this study was to examine the effect of adding vaname shrimp shells on wheat flour tekwan on its sensory preference levels, including color, aroma, taste, and texture, with treatments of 75 g, 100 g, and 125 g. The testing method used was a hedonic test with a Likert scale of 1-5 on 30 untrained panelists. Data were analyzed using ANOVA at a 5% confidence level and Duncan's multiple range test. Based on the test results at a 5% confidence level, it was found that the addition of shrimp shells did not affect the preference for color (Fcount 1.91< Ftable 3.15) and texture (Fcount 0.52 < Ftable3.15) of wheat flour tekwan at 75 g, 100 g, and 125 g; it affected aroma (Fcount 3.41 > Ftable 3.15) and taste (Fcount 3.65 > Ftable3.15) of wheat flour tekwan at 75 g, 100 g, and 125 g. The 125 g treatment was preferred over the others with an an average preference score of 3.97 (liked) for color; 3.93 (liked) for aroma; 4.2 (liked) for taste; and 3.97 (liked) for texture.